Study of Two-wheel Vehicle’s fuel consumption under the Influence of tire Inflation Pressure - Bhat, Samir Ali Roy; Bhandari, Shraddha; Bastakoti, Durga (Journal of Engineering and Sciences, 2024)
The value of air pressure in the tire not only supports the entire weight of the vehicle, it also plays a crucial role in improving the vehicle’s performance, reducing friction, providing comfort, boosting economy and enhancing safety. This study deals with the influence of tire inflation pressure on fuel consumption at various road conditions and speeds. The experimental test was performed riding a motorcycle of 180cc and using a mileage measuring kit to find the effect of tire pressure on three different road surfaces i.e., highway, earthen and graveled. The standard tire pressure for both front and rear tires recommended by the manufacturing company was also evaluated to observe the change in mileage. The results showed that the highest mileage of 55.97 km/L was obtained on the highway among the defined three road conditions and a linear drop of 5psi in tire pressure led to loss of mileage up to 6.11% in highway, 5.35% in earthen and 2.80% in graveled road. Also, the variation in speed resulted to compensation of mileage by nearly 39.9% maximum. These results highlight the importance of keeping the correct value of tire inflation pressure in relation to fuel consumption.